1997
DOI: 10.1071/a96119
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting methane production in Brahman cattle by dietary supplementation with a novel compound and the effects on growth

Abstract: Three experiments were conducted to determine the effects of dietary supplementation with a novel antimethanogenic compound (AM) on methane production and growth in Brahman (Bos indicus) steers. The compound was a chemical complex of bromochloromethane (BCM) and α-cyclodextrin, which is chemically stable when added to feed, thus overcoming the highly volatile nature of BCM. In these experiments the AM compound was administered to steers as a mixture with different feed supplements. In Expt 1 the effect on in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 16 publications
9
68
0
1
Order By: Relevance
“…A gradual decrease in methane output was observed with an increasing concentration of BES (1-40 mM), whereas methane output was not detectable at a BCM concentration of !5 mM. If there is a connection between this observation and the known persistency of BCM as an inhibitor of methane emissions, as shown in vivo (McCrabb et al 1997), as compared with a lack of persistency observed for BES (Van Nevel and Demeyer 1995), the development of future inhibitors of enteric methanogenesis would warrant closer attention to the mode of action of BCM. The extent of reduction in methane output with increasing concentration of BES was more pronounced for GS+B than for ryegrass.…”
Section: Halogenated Methane Analogues (Hma) and Pyromellitic Diimidementioning
confidence: 99%
See 1 more Smart Citation
“…A gradual decrease in methane output was observed with an increasing concentration of BES (1-40 mM), whereas methane output was not detectable at a BCM concentration of !5 mM. If there is a connection between this observation and the known persistency of BCM as an inhibitor of methane emissions, as shown in vivo (McCrabb et al 1997), as compared with a lack of persistency observed for BES (Van Nevel and Demeyer 1995), the development of future inhibitors of enteric methanogenesis would warrant closer attention to the mode of action of BCM. The extent of reduction in methane output with increasing concentration of BES was more pronounced for GS+B than for ryegrass.…”
Section: Halogenated Methane Analogues (Hma) and Pyromellitic Diimidementioning
confidence: 99%
“…For example, chloral hydrate led to liver damage and death in sheep after prolonged feeding (Nagaraja et al 1997) but there has been no adverse effects on rumen fermentation when BCM was fed to either steers (McCrabb et al 1997) or goats (Abecia et al 2012). Therefore, the toxic effects of all HMA need to be assessed in vivo on a compound by compound basis.…”
Section: Halogenated Methane Analogues (Hma) and Pyromellitic Diimidementioning
confidence: 99%
“…However, this approach is technically difficult, given the cumbersome techniques required to grow methanogens, their inherently slow growth kinetics and their extreme sensitivity to oxygen. Historically, a number of studies using various halogenated compounds have demonstrated the 'proof of principle' of small molecule inhibitors, especially in shorter-term animal experiments; however, unfortunately, the inhibitors are either unacceptable because of environmental or toxicology concerns, or tend to become less effective over time (Johnson et al, 1972;Czerkawski and Breckenridge, 1975;Van Nevel and Demeyer, 1995;McCrabb et al, 1997).…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…However its long-term effects must be evaluated. McCrabb et al (1997) studied the effect of a chemical complex of bromo-chloromethane and cyclodextrin, which is chemically stable when added to feed, and reported that these two compounds as a complex reduced CH 4 production without any negative effect on fiber digestion. Longer lasting effects of chemical agents may offer an avenue for mitigating enteric CH 4 production, but public health concern about chemical residues in milk will have to be addressed.…”
Section: Direct Inhibition By Chemicalsmentioning
confidence: 99%